Inhibition of LPS-induced chemokine production in human lung endothelial cells by lipid conjugates anchored to the membrane - Beck, Grietje; Yard, Benito A.; Schulte, Jutta; Oberacker, Ralph; Ackern, Klaus van; Woude, Fokko J. van der; Krimsky, M; Kaszkin, M; Yedgar, S (British journal of pharmacology, 2002)
In acute respiratory distress syndrome (ARDS) induced by endotoxins, a high production of inflammatory mediators by microvascular lung endothelial cells (LMVEC) can be observed. Activation of cells by endotoxins may result in elevated secretion of phospholipase A2 (sPLA2) which is thought to contribute to tissue damage. The present study was undertaken to investigate the role of sPLA2 in chemokine production in human lung microvascular endothelial cells (LMVEC) stimulated with the endotoxins lipopolysaccharide (LPS) and lipoteichoic acid (LTA). In particular, we investigated the effects of sPLA2 inhibitors, specifically, the extracellular PLA2 inhibitors (ExPLIs), composed of N-derivatized phosphatidyl-ethanolamine linked to polymeric carriers, and LY311727, a specific inhibitor of non-pancreatic sPLA2.